Quarterly bulletin on food price dynamics, inflation, and the food security situation in Sudan: 2021Q1- 2022Q4 - Ahmed, Mosab O. M.; Siddig, Khalid (International Food Policy Research Institute, 2023)
-Average international prices of wheat, sorghum, rice, and sugar slightly increased in Q4 of 2022 compared to Q3. Import parity prices decreased during the same period because of the reduction in the freight cost to Port Sudan. -Annual inflation2 decreased from three-digit inflation (260.6 percent) in 2022Q1 to 92.6 percent in 2022Q4. -Quarterly changes in the price of non-volatile commodities (core inflation) 3 increased slightly in Q4 compared to Q3 of 2022 due to the increase in the housing rents, education, communication, and processed food prices. -Retail prices of food commodities were relatively stable during the last two quarters of 2022 com pared to the previous quarters of 2021 and 2022. -Nominal wholesale prices of grains in Khartoum State increased gradually from 2021Q2 to reach a peak in 2022Q3, before dropping in real and nominal terms in 2022Q4. -Although the national average of causal labor daily wage was increasing over time nominally (2021Q2–2022Q4), it was decreasing in real terms in 2022Q4. -Poorer urban and rural households (bottom 40 percent) were more affected by the changes in the prices of food and beverage commodities during 2022Q4 than richer households (top 60 percent). -Blue Nile, Darfur, and Eastern regions have the highest food insecure population classified in crisis or emergency.